The need for permanent pacemaker after restoration of conduction following atrioventricular block: a retrospective cohort study - Ali Bozorgi; Sajad Ahmadzadeh; Seyedeh Hamideh Mortazavi; Saeed Sadeghian; Ali Vasheghani Farahani; Kaveh Hosseini; Arash Jalali; Keyvan Ghasemi; Mehdi Mehrani; Masih Tajdini (KARE Publishing, 2020)
Objective: A permanent pacemaker (PPM) is necessary for patients with a symptomatic third-degree or advanced second-degree atrioventricular (AV) block. An AV block due to medication use can often be reversed; however, subsequent relapse can occur and necessitate subsequent PPM implantation. The aim of this study was to explore the course and prognosis of patients with an AV block. Methods: This historical cohort study was conducted between January 2013 and June 2018. A total of 1900 patient records were analyzed and 1123 subjects with an AV block on admission were enrolled. The patients were categorized into 2 groups: Group 1 comprised patients with an AV block due to medication use (n=316, 28%) and Group 2 included patients with an AV block caused by other etiologies (n=807, 72%). Data of the cause of AV block, recurrence, and PPM implantation were analyzed. Patients in both groups who did not require a PPM during the index admission were followed up regarding subsequent implantation of a PPM. Results: AV conduction was recovered in 38 (12%) patients in Group 1 and 48 (6%) patients in Group 2 during the index hospitalization. However, recurrence of the AV block was observed in 18% of Group 1 patients and 40% of Group 2 patients. Only 25 patients in each group (4.5% of the whole study population) remained PPM-free during a median 3-year follow-up period. Conclusion: The study findings suggest that drug-induced AV blocks may not be as benign as previously thought. The high relapse rate indicates that watchful follow-up may be required despite discontinuation of the responsible medication and that consideration of earlier PPM implantation in cases of early recurrence may be warranted.